Lukashiv T.O., Yurchenko I.V., Yasynskyy V.K. Necessary and Sufficient Conditions of Stability in the Quadratic Mean of Linear Stochastic Partial Differential-Difference Equations Subject to External Perturbations of the Type of Random Variables // Cybernetics and System Analysis.– 2020.– Vol. 56, Iss. 2.– P.303–311. - Yasynskyy, Volodymyr Kyryllovych; Yurchenko, Igor Valeryjovych; Lukashiv, Taras Olegovych (Springer Science+Business Media, LLC, 2020)
It is obtained the necessary and sufficient conditions for the stability in the mean square of the strong solutions of stochastic differential-difference equations with partial derivatives with pairwise independent external random distributions of random variables type.
Одержано необхідні та достатні умови стійкості в середньому квадратичному сильних розв’язків стохастичних диференціально-різницевих рівнянь з частинними похідними з попарно незалежними зовнішними випадковими збуреннями типу випадкових величин.
Keywords: stochastic partial differential equation, stability in the mean square, random perturbation